Zamzam Water Surpasses Global Standards in Quality and Mineral Content - Hassan , Abed Sultan; Ali , Nadia Abd Ellatif (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the physical, chemical, and bacteriological properties of Zamzam tap water and two popular bottled waters,